MORAL VALUE AND CHARACTER-BUILDING EDUCATION IN FOLKLORE: SI GALE GALE - Nur Jannah; Sri Karolina Br Surbakti; Aryani Monita Tarigan; Achida Niasti Veronica Gulo (English Language Teaching Prima Journal (ELT), 2020)
In character building education and moral values there are significant things that are writtenin the meaning of folklore as a characteristic of a culture. The aim of this study is to describefolklore as a way to build character education and increasing moral values into an education.SIGALE-GALE PEOPLE'S STORIES FROM TAPANULI UTARA as source of data in thisresearch. After analyzing and recording important points in the story through a qualitativedescriptive method, several things can be obtained that contain character building educationand moral values in the SIGALE-GALE story: individual, social, and religious moral values.Which can be applied in attitudes and behaviors in character building education.This research uses the technique of content analysis, which is a research analysis that revealsthe ideas of the author or creator, both manifestly and latently. There for, it can be concludedthat the SIGALE-GALE folklore apart from being an education to build character and moralvalues can also be a means of getting to know ancestors and their stories for futuregenerations.Keywords: character buiding education, moral value, folklore, SIGALE-GALE.